2022
DOI: 10.3390/v14061261
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Pseudomonas Phage Pf4 in the Context of Therapy-Inducibility, Infectivity, Lysogenic Conversion, and Potential Application

Abstract: More than 20% of all Pseudomonas aeruginosa are infected with Pf4-related filamentous phage and although their role in virulence of P. aeruginosa strain PAO1 is well documented, its properties related to therapy are not elucidated in detail. The aim of this study was to determine how phage and antibiotic therapy induce Pf4, whether the released virions can infect other strains and how the phage influences the phenotype of new hosts. The subinhibitory concentrations of ciprofloxacin and mitomycin C increased Pf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Indeed, when Pf4* was added to P. aeruginosa cultures, the bacteria showed lower cytotoxicity and virulence in mice ( 24 ), as well as reduced production of the siderophore pyoverdine ( 35 ). Interestingly, a recent study shows that Pf4 phages influence many virulence factors of newly infected P. aeruginosa strains, with the exception of swimming motility and biofilm production ( 36 ). In addition, it was recently shown that the superinfection exclusion protein PfsE binds to PilC to avoid extension of the of type IV pili, hence affecting twitching motility ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, when Pf4* was added to P. aeruginosa cultures, the bacteria showed lower cytotoxicity and virulence in mice ( 24 ), as well as reduced production of the siderophore pyoverdine ( 35 ). Interestingly, a recent study shows that Pf4 phages influence many virulence factors of newly infected P. aeruginosa strains, with the exception of swimming motility and biofilm production ( 36 ). In addition, it was recently shown that the superinfection exclusion protein PfsE binds to PilC to avoid extension of the of type IV pili, hence affecting twitching motility ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, acute infection of P. aeruginosa by the Pf4 bacteriophage inhibited the production of the virulence factor pyoverdine ( 35 , 40 ). Recently, it was shown that Pf4 phages were produced in larger amounts upon exposure to sublethal concentrations of ciprofloxacin and mitomycin C ( 36 ). Interestingly, the released Pf4 virions were able to successfully infect new strains of P. aeruginosa , establishing very complex interactions with other indigenous filamentous (pro)phages ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SI-Pf variants emerge spontaneously under stress conditions. This is due to mutations in the phage genome that result in excision from the bacterial chromosome with subsequent dysregulation of replication (23, 24). Along such lines, we have reported that a P. aeruginosa mutant lacking the mismatch repair enzyme MutS spontaneously produced SI-Pf at a high frequency (25).…”
Section: Resultsmentioning
confidence: 99%